Pengaruh Kualitas Pengembangan Minat Bakat Siswa Dan Fasilitas Sekolah Terhadap Keputusan Pelanggan Pada PKBM Generasi Juara Di Depok - Yustifara, Shilvy; Wijoyo, Agung (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. The purpose of this study was to determine the effect of the quality of student talent interest development and school facilities on customer decisions at PKBM Generasi Juara in Depok, both partially and simultaneously. This research method uses quantitative methods with a sample size of 85 respondents, the data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, simple correlation coefficient test, multiple correlation coefficient test, coefficient of determination analysis test, t test and f test. Based on the results of the t test, the t count is 10.260> 1.989 and the significance value for the student talent interest variable (X1) is 0.000, the significant value is smaller than the probability value of 0.05 or 0.000 <0.05, meaning that the student talent interest variable (X1) has a positive and significant effect on the customer decision variable (Y). at PKBM Generasi Juara in Depok. Based on the results of the t test, the t value is 9.879> 1.989 and the significance value for the school facilities variable (X2) is 0.000, the significance value is greater than the probability value of 0.05 or 0.000 <0.05, meaning that the school facilities variable (X2) has a positive and significant effect on the customer decision variable (Y). at PKBM Generasi Juara in Depok. Based on the results of the f test, the calculated f value is 81.621> 3.11 and a significance value of 0.000 <0.05. So it can be concluded that the variables of student talent interest (X1) and school facilities (X2) simultaneously have a positive and significant influence on customer decisions (Y). at PKBM Generasi Juara in Depok Keywords: Quality of Student Talent Interest Development, School Facilities Customer Decision